2015
DOI: 10.1007/978-3-319-11128-5_143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Liver Vasculature on Electric Field Distribution during Electroporation Treatments: An Anatomically Realistic Numerical Study

Abstract: Abstract-Electroporation is the phenomenon in which cell membrane permeability is increased by exposing the cell to high intensity electric fields. In living tissues, such permeabilization boost can be used in order to enhance the penetration of drugs or DNA plasmids or to destroy undesirable cells and it is typically performed by applying pulsed high voltages across needle electrodes. When used for ablation, and particularly in the context of liver tumors, it is often claimed that in contrast with thermal abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In a past numerical study focused on liver ablation by irreversible electroporation (IRE), we noticed that, although the presence of large blood vessels does not distort very significantly the treated volume, sub-lethal regions (i.e. too low electric field magnitude) can appear around the blood vessels [2]. The presence of such sub-lethal regions has also been reported recently in another numerical study [3].…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…In a past numerical study focused on liver ablation by irreversible electroporation (IRE), we noticed that, although the presence of large blood vessels does not distort very significantly the treated volume, sub-lethal regions (i.e. too low electric field magnitude) can appear around the blood vessels [2]. The presence of such sub-lethal regions has also been reported recently in another numerical study [3].…”
Section: Introductionsupporting
confidence: 53%
“…Interestingly, the differences are larger where the sublethal regions appeared around the blood vessels in the IRE study reported in [2]. That is, at the vessel poles perpendicular to the electric field (axis defined by the two electrodes).…”
Section: A 2d Simulation Resultsmentioning
confidence: 80%
See 3 more Smart Citations